The Use of Question-Answer Realationship Strategy for Teaching Reading Text for English Students of Excel English Sidoarjo - Saiselar, Hentriyana Dorsila; Afri, Evan (ITScience (Information Technology and Science), 2024)
The objectives of this research are to know and to describe the implementation of teaching reading comprehension by using the QAR strategy, to know and to describe the advantages and the disadvantages of teaching reading by using the QAR strategy for the eleventh-grade students of EXCEL ENGLISH Sidoarjo. This research used a qualitative research method. The data is in the form of the implementation of the QAR Strategy by teachers as well as the advantages and disadvantages regarding the implementation of the QAR Strategy. In collecting the data, this research used three kinds of instruments: observation, interview, and documentation. This research used three major phases of data analysis: data reduction, data display, and conclusion drawing or verification. The results of the research are as follows: The first is that the teaching and learning processes in the class ran well. It could be seen that the teacher completed the QAR step based on Margareth’s procedure of teaching reading by using the QAR strategy. In the atmosphere of teaching and learning reading by using the Question-Answer Relationship strategy, the students looked active and responsive to the teacher. Second, the QAR Strategy has been proven to have benefits in helping students improve their reading, and there are only a few disadvantages to the QAR Strategy. Namely, the teacher has to explain the existence of several types of QAR Strategy questions.